Modelling of the risk factors and chronic diseases that influence the development of serious health complications - Atanasijević-Kunc, Maja (Zdravniški vestnik, 2008)
Some chronic diseases, like diabetes type 2 and hypertension, and risk factors, such as obesity, hypercholesterolemia, and smoking, are strongly correlated with the potential development of serious health complications thatcan threaten a patient š life or significantly influence the quality of life, while at the same time representing an enormous economic burden. Such complications include, for example, stroke, coronary heart disease, peripheralarterial vascular disease, end-stage renal disease and congestive heart failure. For a quantitative evaluation of the mentioned patient groups, the age distribution and an estimation of the treatment expenses a dynamic mathematical model was developed, where special attention was devoted to its structure, as it should enable the sequential construction and representation of different forms of data information. The model was realized in the Matlab program package with the Simulink Toolbox. A dynamic mathematical model is described that enables the observation of patients (in percentage terms) with diabetes type 2 and obesity, as well as those who smoke, have hypercholesterolemia and hypertension and all possible combinations of these problems, related to their age. Taking into account the Slovenian demographic data and annual treatment expenses, we were able to quantitatively evaluate these factors, not only in Slovenia but also in other developed regions where the demographic and economic situations are similar. It is also possible to extend the model to patients with serious complications, also taking into account the population dynamics, which is the goal of the nextsteps in our investigation. (Abstract truncated at 2000 characters)
Keywords: bolezni; chronic condition; Chronic Disease; Computer Simulation; Debelost; dejavniki tveganja; Diabetes Mellitus, Non-Insulin-Dependent; disease; Health Care Costs; Hiperholesterolemija; Hipertenzija; Hypercholesterolemia; Hypertension; Kajenje; Kronična bolezen; modeliranje; Obesity; Računalniška simulacija; simulacija; Sladkorna bolezen, ne-inzulin-odvisna; Smoking; zapleti; Zdravstveno varstvo, stroški